Relationship between Education, Mother's Knowledge and Environmental Sanitation with Stunting for Toddlers in the Sarudik Primary Care Area Central Tapanuli Regency in 2020 - Herlina Tarigan (Institute of Computer Science (IOCS), 2021)
Stunting describes chronic undernutrition status during growth and development since early life. This situation is represented by a z-score of height for age (TB/U) less than -2 standard deviations (SD) based on growth standards. Based on the results of a preliminary survey study conducted at the Sarudik Primary care in February 2020, it was found that the number of toddlers was 60 people with stunting incidence as many as 16 toddlers. Based on the data above, the researchers examined the relationship between education, maternal knowledge and environmental sanitation with stunting in toddlers in the area of the Sarudik Primary care, Central Tapanuli Regency in 2020. This type of research is analytic observational with a cross sectional approach (cross-sectional). With a sample of 60 children aged 6-23. This study uses the chi square statistical test. showed the incidence of stunting in children under five as many as 14 respondents (41.2%). Respondents who are less knowledgeable about the incidence of stunting in toddlers are 16 people (36.4%). Environmental sanitation in good respondents who experienced stunting as many as 2 people (6.9%) and poor environmental sanitation who experienced stunting as many as 15 people (48.4%). The variables of education, knowledge and environmental sanitation were related to the incidence of stunting, because the p value <0.05.